Expressional accentuations in quotes as applied in Czech scientific and theoretical texts - Schacherl, Martin (Bohemistyka, 2018)
The paper explores the style of a selection of contemporary Czech scientific texts representing contemporary Czech scientific discourse, which comprises professional monological monographs written in Czech in the last decade. Through exploring a re- presentative selection of texts, our research endeavoured to verify the occurrence or non-occurrence of linguistic concern which is deliberately used in contemporary Czech scientific discourse to interrupt (1) the emotional and stylistic neutrality and (2) the relative comprehensiveness, lucidity and clarity of the professional expression. Linguistic concern and stylistic activation in contemporary professional texts are in most cases signalled graphically, by quotation marks. The authors thus indicate to the recipient the occurrence of a stylistic marker, or generally dissimilarity of stylistic norms. Formal separation of the device from the text is an important dialogical means connecting the author and the recipient of scientific discourse. Most often it features simplifying terminology; (non)exact expression; complementarity; the vacillating or transient terminology in the field. The authors use quotation marks to signal graphically not only means that are contradictory to scientific style, such as professionalisms; expressions meaning ‘so as to say’; imprecise, ambigous and vague expressions (which in humanities and social sciences occur in the foundation text); but also means of expression conveying subjectivity and expressivity; sporadically meta- phors. Humanities and social sciences even feature graphically signalled authorian detachment from the content; hyperbole; or possibly irony. The stylistic activity of the quoted means of expression consists in their manifest contextual stylistic value. Manifest activity of diverse linguistic means separated by quotation marks represent the most forceful way to activate the neutral presentation of present-day Czech profesional texts. Their frequency and stylistic activity in all excerpted monographs in the defined groups of fields confirm the authorial ambition to achieve a more original diction of professional discourse. The graphical distinction from the foundation text proves the continuous respect for the stylistic norms of theoretically professional communication.